Our Experience of Eight Patients with Dural Arteriovenous Fistula's at Foramen Magnum with Respect to Presentation, Angioarchitecture, and Endovascular Treatment Outcomes - Mundhe, Vijay Madhukar; Singh, Rakesh Singh; Singh, Neeraj; Karapurkar, Anil; Deshmukh, Narayan; Reddy, Jagdish (Asian Journal of Neurosurgery, 2023)
Background Dural arteriovenous fistulas (DAVFs) around foramen magnum (FM) with peri medullary venous drainage, are uncommon and have wide spectrum of presentation. Literature about this lesion is sparse. We intent to analyze and report our experience with these cases with respect to presentation, evaluation, and endovascular treatment outcomes.Materials and Methods All the eight patients who were diagnosed with DAVFs at FM and treated with transarterial embolization using ethylene viny alcohol were included in this study. Clinical record sheets, radiological, and angiographic data of these patients were retrieved from our departmental database.Results Duration of symptoms ranged from 1 day to 3 years. Presentation with progressive ascending sensory symptoms and weakness (N = 4), acute headache (N = 2) acute quadriplegia (N = 1), and right ear bruit (N = 1) was seen. Exclusive feeders from occipital artery (OA) and vertebral artery (VA) were seen in two and four patients, respectively. Dual feeders from a combination of ascending pharyngeal artery and VA; from a combination of OA and VA were seen in one patient each. The exclusive venous drainage to spinal peri medullary veins (N = 3), brain stem peri medullary veins (N = 1), and both combined (N = 4). Two patients had a draining vein aneurysm. Complete obliteration of fistula was achieved in all patients. Complete resolution of symptoms was seen in six patients; two patients had significant improvement.Conclusion The clinical presentation of dural AVF at foramen magnum is wide ranging and these lesions can be treated effectively and safely by transarterial embolization. Duration of symptoms strongly influences the final patient outcome.
Keywords: dural arteriovenous fistula; foramen magnum; ethylene vinyl alcohol; vertebral artery; occipital artery